2014
DOI: 10.1007/s00204-014-1308-5
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular signal-regulated kinases 1/2 and Akt contribute to triclosan-stimulated proliferation of JB6 Cl 41-5a cells

Abstract: Triclosan is a broad spectrum anti-bacterial agent widely used in many personal care products, household items, medical devices, and clinical settings. Human exposure to triclosan is mainly through oral and dermal routes. In previous studies, we found that sub-chronic dermal exposure of B6C3F1 mice to triclosan induced epidermal hyperplasia and focal necrosis; however, the mechanisms for these responses remain elusive. In this study, using mouse epidermis-derived JB6 Cl 41-5a cells, we found that triclosan sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…It is known that ROS initiates apoptosis and activates various signaling pathways, with the cascaded reactions and crosstalk among multiple cellular events contributing to toxicity associated with certain chemicals [25,[48][49][50][51][52][53][54]. In this present study, we found that two members of the MAPK signaling pathway, JNK and p38, were activated at high and moderate levels, respectively (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…It is known that ROS initiates apoptosis and activates various signaling pathways, with the cascaded reactions and crosstalk among multiple cellular events contributing to toxicity associated with certain chemicals [25,[48][49][50][51][52][53][54]. In this present study, we found that two members of the MAPK signaling pathway, JNK and p38, were activated at high and moderate levels, respectively (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…In agreement with the cytotoxicity data, TCS-treated mouse lung epithelial cells were deformed with reduced viability [83]. Conversely, TCS stimulated the proliferation of mouse epidermis-derived JB6 Cl 41-5a cells, by increasing cyclins D1 and A and reducing p27(Kip1) protein levels [84]. Examining these effects in vivo , B6C3F1 mice exhibited epidermal hyperplasia and focal necrosis following topical administration of TCS.…”
Section: Cellular Longevitysupporting
confidence: 53%
“…However, effects of triclosan on the MAPK pathway vary from different studies. In JB6 Cl 41-5a cells, triclosan at 3 µM stimulated cell proliferation via activating the ERK and Akt pathways, but not the p38 pathway [18]; in neural stem cells, triclosan at 50 µM decreased the cell viability through inducing the phosphorylation of p38 and JNK [15]. We analyze that the diverse effects of triclosan on the MAPK pathway maybe consist in different cells and various concentrations used.…”
Section: Discussionmentioning
confidence: 99%